1996
DOI: 10.2307/2269392
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Hawksbill Turtles in a Caribbean Feeding Area as Indicated by Genetic Markers

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecological Applications.Abstract. Hawksbill turtles move between nesting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 31 publications
1
58
0
2
Order By: Relevance
“…Otros agregados marinos de esta especie en el Caribe (Diez & van Dam 2002, Chacón 2004 y Australia (Limpus 1992, Limpus & Miller 2008) también presentan mezcla de estos estados ontogenéticos, los cuales tienden a ser genéticamente heterogéneos (Bass 1999, Bowen et al 1996, Díaz-Fernández et al 1999. Si utilizamos las ecuaciones de regresión lineal entre el LRC y el LCC (C. mydas: LRC = (0.94 x LCC) + 0.5cm; E. imbricata: LRC = (0.84 x LCC) + 7.63cm) que Lee (2009) determinó para ambas especies en el agregado marino del Archipiélago Jardines del Rey, obtenemos para las hembras prepubescentes de C. mydas y E. imbricata intervalos de LCC de 68.6-98.4cm y 50.4-77.8cm respectivamente.…”
Section: Discussionunclassified
“…Otros agregados marinos de esta especie en el Caribe (Diez & van Dam 2002, Chacón 2004 y Australia (Limpus 1992, Limpus & Miller 2008) también presentan mezcla de estos estados ontogenéticos, los cuales tienden a ser genéticamente heterogéneos (Bass 1999, Bowen et al 1996, Díaz-Fernández et al 1999. Si utilizamos las ecuaciones de regresión lineal entre el LRC y el LCC (C. mydas: LRC = (0.94 x LCC) + 0.5cm; E. imbricata: LRC = (0.84 x LCC) + 7.63cm) que Lee (2009) determinó para ambas especies en el agregado marino del Archipiélago Jardines del Rey, obtenemos para las hembras prepubescentes de C. mydas y E. imbricata intervalos de LCC de 68.6-98.4cm y 50.4-77.8cm respectivamente.…”
Section: Discussionunclassified
“…In these species, once sexual maturity is reached turtles begin periodic migrations between feeding and breeding/nesting areas, which are sometimes separated by thousands of kilometers (Miller, 1997), with females (Carr, 1967), and to a lesser extent males , exhibiting phylopatric or "natal homing" behavior. This has been verified using flipper tags (Limpus et al, 1992;Horrocks et al, 2011), satellite tracking (Luschi et al, 2006;Godley et al, 2010) and mtDNA markers Bowen et al, 1996), in which has demonstrated significant differences in the mtDNA haplotype frequencies among nesting populations (Bowen and The Wider Caribbean has also been the scene of political conflict in the management of E. imbricata. The majority of WC nations had already abandoned the legal fishery for this species when Cuba permanently closed its legal fishery in January 2008.…”
Section: Introductionmentioning
confidence: 86%
“…To assure broad comparisons of our results with previous studies, our control region sequence alignment was trimmed to 384 bp of length. Haplotype designation followed that from previous publications Bowen et al, 1996Bowen et al, , 2007bDíaz-Fernández et al, 1999;Browne et al, in press). Deletion in haplotype D at position 59 and a 10-bp insertion at position 354 in haplotype MX1A were treated as single substitutions following Bowen et al (2007b).…”
Section: Methodsmentioning
confidence: 99%
“…* indicates the total number of samples including hybrids with loggerhead turtle haplotypes R, S, T and U. Literature references: Bowen et al, 1996;Díaz-Fernández et al, 1999;Troëng et al, 2005;Bowen et al, 2007b;Browne et al, in press). haplotype network to obtain further insights into the haplotype relationships.…”
Section: Methodsmentioning
confidence: 99%